The doctor who would be king - Lachenal, Guillaume, 1978- (Theory in forms., 2022)
"The Doctor Who Would Be King, the English-language translation of Guillaume Lachenal's Le Médecin qui voulut être roi, tells the story of Dr. Jean Joseph David, known as "King David" or the "Emperor of Haut-Nyong," and the experiment in colonial governance he led. From 1939-1944, the Haut-Nyong area of French Cameroon was placed under the authority of David and five other French doctors. Expanding efforts to rein in epidemics that had depopulated the region, David was given authority to refashion the Medical Region as a laboratory for a utopian dream at the heart of European colonialism: the fantasy that colonial powers would emancipate their colonies from misery, ignorance, and sickness. David was thus freed from political and military influence to reform government, law, and economy according to his vision of rational public health policy-and he used this mandate to build hospitals, introduce new crops, and implement totalitarian control and violence. Drawing on African and Pacific histories, environmental humanities, and critical global health, Lachenal situates Dr. David's experiment in the context of French imperialism, examining its precedents and afterlives from the Polynesian islands to post-war Africa. He traces the destiny of a failed utopia, interweaving David's biography with a captivating account of his fieldwork to unearth the traces it left in contemporary places, objects, songs, memories, and ruins"--